Onshore power supply–trends in research studies - Kizielewicz, Joanna (Frontiers in Energy Research, 2024)
Restrictive regulations introduced by the European Parliament and the United Nations have forced the seaport authorities to reach net zero gas emissions by 2030. An important source of pollution emitted in ports involves exhaust gas emissions from ships powered by ship engines while they are berthed in seaports. One of the ways to reduce the level of pollution and nuisance caused by ship engines is to equip ships with Onshore Power Supply (OPS). Unfortunately, still few ports can boast this type of systems at their quays. There are many publications devoted to the analysis of this phenomenon in the technical and engineering terms, but a significant part also concerns the economic, financial, logistic and organizational aspects. The aim of this research is to identify the directions of development as for research into OPS, to organize the terminology devoted to OPS, and to define scientific disciplines of research in the field of OPS. This research was conducted on the basis of the data mining method using the Scopus, EBSCO and Web of Science databases, applying the multi-stage selection of criteria. The research results may provide an interesting material for scientists to identify the gaps of research regarding OPS.